High-efficiency perovskite solar cells with poly(vinylpyrrolidone)-doped SnO2 as an electron transport layer. Issue 4 (22nd June 2020) - Zhang, Meiying; Wu, Fengmin; Chi, Dan; Shi, Keli; Huang, Shihua
Abstract : Hybrid organic–inorganic perovskites have attracted intensive attention as the absorber layer in high-performance perovskite solar cells (PSCs). Abstract : Hybrid organic–inorganic perovskites have attracted intensive attention as the absorber layer in high-performance perovskite solar cells (PSCs). The interface between the electron transport layer and the perovskite layer in perovskite solar cells has a large effect on the device performance. Herein, we report a perovskite solar cell with a cell structure of ITO/ETL/(FAPbI3 )0.97 (MAPbBr3 )0.03 /spiro-OMeTAD/MoO3 /Ag, where the poly(vinylpyrrolidone) (PVP)-doped SnO2 film works as the electron transport layer. We observe that the perovskite film grown on PVP-SnO2 shows more uniform crystalline grains than the control sample grown on the pure SnO2, and the electron mobility of the PVP-SnO2 film is higher than that of the pure SnO2 film; consequently, PVP-SnO2 can efficiently extract electrons from the perovskite layer. As a result, the PSCs using the PVP-doped SnO2 ETL showed an increased power conversion efficiency (PCE). The optimized device using the PVP-SnO2 electron transport layer shows an improved PCE of 19.55%, while the PSC using the SnO2 electron transport later shows a PCE of 17.50%. Furthermore, it is feasible to add PVP into the electron transport layer of SnO2 to improve the performance of the planar perovskite solar cell device.